Covid-19 and online classes: Measuring Indian parents’ attitude towards online classes at kindergarten and junior school level - Eliza Sharma (Knowledge Management & E-Learning: An International Journal, 2023)
The study aims to examine the readiness of Indian parents towards online classes at kindergarten and junior school levels, by identifying the perceived barriers, perceived effectiveness and health impact of online classes on young children. The study is based on data collected across a random sample of 750 parents of students studying at junior and kindergarten levels in urban private schools which offer online classes. The data was analyzed through exploratory factor analysis, ANOVA and multiple regression analysis. Technological, infrastructural, and personal barriers related to students, and parents, were identified as perceived barriers by parents in availing online classes for their kids. Parents’ attitude towards online classes at kindergarten and primary levels gets negatively influenced by the barriers they face, and the perceived negative impact of technology usage on their kids’ health, while; perceived effectiveness was found to have a positive impact on the parents’ attitude. The study is unique as it includes the interest of such young stakeholders of the education system. The study highlights the barriers faced by parents related to online classes and the health-related concerns which play a major role in the adoption of online mode of education for their kids. Research gives insights to school authorities and the government to work on these barriers and make the online education system effective which is the need of the hour during COVID-19.